1974
DOI: 10.3181/00379727-145-37954
|View full text |Cite
|
Sign up to set email alerts
|

Significant Effect of Environmental Lighting on Caries Incidence in the Cotton Rat

Abstract: Dental caries is a multifactorial disorder, the initiation and progression of which are affected by factors related to host susceptibility, oral microflora, and diet. Interlocking triple rings are frequently employed to demonstrate that microorganisms, fermentable carbohydrates, and a susceptible tooth surface are all requisite in the caries process. It is well established that lesions do not develop in gnotobiotic animals and that dietary modification such as carbohydrate restriction significantly restricts c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1978
1978
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…This study was later confirmed in the second year of the Sarasota school study (Mayron et al 1975). A follow-up study on cotton rats by Feller, Edmonds, Shannon, and Madsen (1974) showed similar results with either Vita-lite or incandescent lights. Thus either the red of incandescent lamps or of Vita-lite and/or the ultraviolet of Vita-lite is essential to increase body resistance to caries, or the midrange maximum of cool-white lamps has a deleterious effect on resistance to caries.…”
Section: Other Effects Of Lightsupporting
confidence: 82%
“…This study was later confirmed in the second year of the Sarasota school study (Mayron et al 1975). A follow-up study on cotton rats by Feller, Edmonds, Shannon, and Madsen (1974) showed similar results with either Vita-lite or incandescent lights. Thus either the red of incandescent lamps or of Vita-lite and/or the ultraviolet of Vita-lite is essential to increase body resistance to caries, or the midrange maximum of cool-white lamps has a deleterious effect on resistance to caries.…”
Section: Other Effects Of Lightsupporting
confidence: 82%
“…Studies on rodents do not generally support this hypothesis (Sharon et al, 1971;Feller et al, 1974), and research on humans provides mixed results. Mayron et al (1975aMayron et al ( , 1975b found fewer dental caries over one school year in first-and second-graders whose windowless classrooms had radiation-shielded FSFL, compared to unshielded CWFLs.…”
Section: Vitamin D and Calcium Metabolismmentioning
confidence: 87%
“…Currently, it is not known whether a distorted light spectrum affects the health, behaviour, or welfare of laboratory rodents. The literature carries conflicting reports of consequences for dental health (Sharon, Feller, and Burney 1971;Feller et al 1974), growth and development (Wurtmann and Weisel 1969;Ozaki and Wurtman 1979;Saltarelli and Coppola 1979).…”
Section: Vision and Housingmentioning
confidence: 99%